John Lennon : Unseen Archives - Clayton, Marie and Thomas, Gareth (Bath ,England Parragon Publishing, 2002)
"John Lennon: Unseen Archives comprehensively chronicles the life of the world's most famous pop-star peace campaigner. The majority of the photographs are from the archive of the Daily Mail and they are accompanied by a detailed commentary which provides an insight into how John Lennon became more than a musician and went on to influence an entire generation. This wonderful book captures the impact he made upon the world; the memories of which still linger with us today."--Jacket.
Include Bibliography and Illustration
Keywords: Rock musicians -- Lennon, John, 1940-1980 -- England